DATA-DRIVEN DECISION MAKING IN DIGITAL MEDIA MANAGEMENT - Dixit, Deepa; Srivastava, Priyanka; Kulkarni, Swapnali Amol; Raju (ShodhKosh: Journal of Visual and Performing Arts, 2025)
This paper explores Data-Driven Decision-Making (DDDM) in the context of digital media management as a case study of Netflix using the DECAS framework, the Decision-Making Process, the Decision Maker, Decision, Data, and Analytics. It examines how the decision ecosystem at Netflix evolved into an adaptive, feedback-driven process through the application of data analytics and machine, and evidence-based strategies in place of the intuition-based decisions previously applied. The study combines both quantitative performance indicators and qualitative organizational findings through the use of a mixed-method approach to determine the effectiveness of DDDM. The results show that Netflix is an analytically mature company in every aspect of DECAS, having achieved an optimal process of decision (readiness score 5/5) and experiencing substantial performance benefits: the level of user engagement grew by 78 percent, the churn rate decreased by 45 percent, content completion improved by 37 percent, and customer satisfaction got 92 percent. The high positive correlation (r = 0.89) between DDDM preparedness and performance results supports the fact that analytics are beneficial factors to improve strategic agility and creative efficiency. The research concludes that Netflix has managed to achieve a sustained success because the company has adopted the factor of human creativity and algorithmic intelligence, made possible by data literate culture and decentralized decision-making as well as a robust data governance. The DECAS framework, therefore, can be used to model organizations interested in creating digital media analytical resilience and innovation capability.